Chromatic and flicker threshold changes in age-related macular degeneration following anti-VEGF treatment - Yadav, Gayatri; Narayanan, Raja; Hathibelagal, Amithavikram R (Clinical and experimental optometry, 2022)
Red-green chromatic sensitivity and photopic (cone-mediated) flicker sensitivity showed marked improvement after anti-VEGF treatment. The use of flicker and chromatic sensitivities as potential functional tests to monitor treatment outcomes in age-related macular degeneration highlights the clinical importance. High-contrast visual acuity (VA) is not a sensitive clinical marker in the management of age-related macular degeneration (AMD). Therefore, flicker and chromatic sensitivity changes were assessed following anti-VEGF treatment in subjects with neovascular AMD. Subjects diagnosed with neovascular AMD were recruited. VA was measured using a COMPlog chart. Flicker (in central 5°) and chromatic thresholds (red-green and yellow-blue) were measured using Flicker-plus test and Colour Assessment and Diagnosis (CAD) tests, respectively. Baseline thresholds and foveal thickness were measured on the same day, just before anti-VEGF injection delivery and 5 weeks ± 5 days later. Thirteen subjects (8 males, 5 females) with a mean age of 67.5 ± 8.2 years completed the study. Median VA was not significantly different post-treatment (0.57 logMAR [~6/22: Snellen equivalent], IQR: 0.33) compared to baseline (0.56 logMAR, IQR: 0.33), Wilcoxon matched-pair test, p = 0.55). Median Red-Green thresholds improved significantly post-treatment (22.15 CAD units, IQR: 26.06, n = 9), compared to baseline (24.24 CAD units, IQR: 26.21, p = 0.02). Median photopic and mesopic FMT did not show significant change post treatment compared to baseline (p > 0.01, statistical significance of p-value corrected for multiple comparisons was set to 0.01). Similarly, the foveal thickness was not significantly different at post-treatment visit than baseline (p = 0.53). Red/green sensitivity recovered better than yellow/blue sensitivity, thus, providing insight into recovery mechanisms in AMD and usefulness of these tests as clinical markers in the management of AMD.